Gatewatching and Collective Curation: Selecting Popular Radio Journalism Sources at Bandnews Rio FM - Vaz Chagas, Luan José (Brazilian journalism research, 2018)
The article presents the results from a systematic observation of and interviews with journalists who produce local radio news program, BandNews FM, in Rio de Janeiro. The objective is to analyze how the gatewatching process is applied to selecting sources from WhatsApp, and to explore the specific nature of work carried out in radio journalism newsrooms. One of the main features of this broadcaster is the large number of public voices selected from the WhatsApp instant messaging application. The data shows popular voices selected for this paper which fit into a particular theme, it shows the collaborative curation with listeners, and it shows the organizational constraints of investigation, highlighted by journalists sitting behind a desk, absent from the stage of the events. Unlike other media vehicles, radio demands continuous updating and decentralization when selecting material to be broadcast. This study points out characteristics that are demanded of journalists who work in radio and the new, newsroom strategies of involving the public via social networking platforms. O artigo apresenta resultados de uma observação sistemática e entrevistas com jornalistas que produzem o radiojornal local da BandNews FM no Rio de Janeiro. O objetivo é analisar como o processo de gatewatching é executado na seleção das fontes via WhatsApp na emissora e as especificidades no trabalho desenvolvido nas redações de radiojornalismo. Uma das principais características apresentadas pela emissora é o alto número de vozes populares selecionadas por meio da interação no aplicativo de mensagens instantâneas. Os dados mostram um encaixe temático das vozes populares selecionadas, a curadoria colaborativa em conjunto com os ouvintes e os constrangimentos organizacionais na apuração com o perfil do jornalista sentado e ausente do palco dos acontecimentos. Ao contrário de outros meios, o rádio demanda de atualização contínua e a descentralização na seleção dos materiais levados ao ar. Nesse sentido, a pesquisa aponta características que o trabalho no ambiente radiofônico demanda dos jornalistas e as novas estratégias desenvolvidas nas redações com o envolvimento dos públicos via plataformas de redes sociais. El artículo presenta resultados de una observación sistemática y entrevistas con periodistas que producen el radio de periodismo local de BandNews FM en Río de Janeiro. El objetivo es analizar cómo el proceso de gatewatching se ejecuta en la selección de las fuentes vía WhatsApp en la emisora y las especificidades en el trabajo desarrollado en las redacciones de radio-periodismo. Una de las principales características presentadas por la emisora es el alto número de voces populares seleccionadas por medio de la interacción en la aplicación de mensajería instantánea. Los datos muestran un encaje temático de las voces populares seleccionadas, la curaduría colaborativa en conjunto con los oyentes y las limitaciones organizacionales en el recuento con el perfil del periodista sentado y ausente del escenario de los acontecimientos. A diferencia de otros medios, la radio demanda de actualización continua y la descentralización en la selección de los materiales llevados al aire. En ese sentido, la investigación apunta características que el trabajo en el ambiente radiofónico demanda de los periodistas y las nuevas estrategias desarrolladas en las redacciones con la participación de los públicos vía plataformas de redes sociales.